Deep foundations on bored and auger piles : BAP III : proceedings of the 3rd International Geotechnical Seminar on Deep Foundations on Bored and Auger Piles, Ghent, Belgium, 19-21 Oct., 1998 /: BAP III : proceedings of the 3rd International Geotechnical Seminar on Deep Foundations on Bored and Auger Piles, Ghent, Belgium, 19-21 Oct., 1998. (2020) - Unknown
No abstract available